ANALISIS POLA KONSUMSI SARAPAN MAHASISWA UPI UNTUK REKOMENDASI LOKASI USAHA SARAPAN - Oktaviani, Dela; Ilham Nursalam, Muhammad; Azzahra, Najla; Hamidah Al Wafaa, Salma; Somantri, Lili; Safarach Bratanegara, Alnidi (Jurnal Bisnis Terapan, 2026)
This study analyzes breakfast consumption patterns of students at the Indonesian University of Education (UPI) and provides location recommendations for breakfast businesses based on spatial and economic factors. The issues raised are students' limited access to affordable, practical breakfast due to high mobility and limited time and cost. The study aims to identify factors influencing breakfast purchasing decisions and produce a map of recommended breakfast business locations around UPI campus. The method used a questionnaire survey of 49 eligible UPI students, analyzed using Geographic Information System (GIS) with buffer techniques, distribution mapping, multilevel symbolization, and instrument validity and reliability tests. Results show that food price, menu variety, and the habit of not cooking are the main drivers of breakfast purchasing decisions. Spatially, breakfast purchasing locations concentrate in front of Koramil and Gegerkalong, while areas with high student concentration such as Gegerkalong Girang still have limited access to breakfast establishments. In conclusion, UPI students' breakfast consumption patterns are uneven and heavily influenced by accessibility and price. It is necessary to develop breakfast establishments in strategic locations such as along student mobility routes to campus and densely populated boarding areas.